LOCAL WISDOM IN THE FLOW OF CAPITALISM IN SHORT STORY “PEMBURU RUSA SEPANJANG PIPA” (KEARIFAN LOKAL DALAM ARUS KAPITALISME PADA CERITA PENDEK “PEMBURU RUSA SEPANJANG PIPA”) - Dessy Wahyuni (Jurnal Gramatika, 2020)
B.M. Syamsuddin, a writer from Riau, Indonesia, presents his ideology through the short story "Pemburu Rusa Sepanjang Pipa (Deer Hunters Along the Pipe)". By promoting local wisdom, he emerged as a defender of the interests of community groups who were marginalized and ignored by the development process in the flow of capitalism. Through this short story, the author describes the discourse of oppression obtained by the people of Riau—represented by the Sakai ethnic group—who cannot enjoy the wealth of their country. This form of defense is seen through the author's ideology that is inserted in the short story. To explore the author's ideology contained in the short story, the writer applies Antonio Gramsci's thoughts on hegemony and dominance with a functional systemic linguistic approach.  Capitalism that brought humans into the process of dehumanization forced society to follow the rules of the game of the rulers. The social values of society are capitalized in the interests of a few people who ultimately marginalize people's lives. From the results of the analysis, it was found that simplicity and ignorance will be suppressed by a power so that local wisdom becomes meaningless. If local wisdom is done wisely, nature will be well preserved, forests will be sustainable, and the balance of ecosystems will form a harmonious life between humans and the natural surroundings.